Identification of Ancient Balinese Settlements of IX-XIV Century Based on Inscription and Toponymy Studies in Tabanan Regency - Ni Ketut Puji Astiti Laksmi; Hedwi Prihatmoko; Zuraidah Zuraidah (Jurnal Kajian Bali (Journal of Bali Studies), 2023)
Settlement has become a very important basic need in human life since humans began living sedentary lives. During the ancient Balinese period of the IX to XIV centuries AD, settlements developed under the rule of ancient Balinese kings. The target of this research is the ancient Balinese settlements based on inscription sources in the Tabanan Regency area, especially the ancient settlements in Lake Bratan, Tamblingan, and Buyan, the Batukaru mountains, and the lowlands in the Tabanan area. The method used in this research is a combination of inscription and toponymy. By tracing the inscriptions, old maps, and RBI maps, as well as the archaeological data currently available, five ancient settlements were found. The five ancient settlements are the villages of Timpag, Bantiran, Batungsel, Batunya, and Mayungan. The results of this research are expected to foster the ability to choose, develop, and maintain settlements and the natural environment around settlements for the sake of the continuity of people's lives, which is also local wisdom that needs to be inherited.